2012
DOI: 10.1111/jac.12010
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration Response of Maize Hybrids to Atmospheric Vapour Pressure Deficit

Abstract: Maize (Zea mays L.) yield is often restricted by low soil water availability, particularly late in the growing season. To increase yields, genetic options for more effective use of available soil water are being explored. One option is to select genotypes that have restricted transpiration rate under high vapour pressure deficit (VPD) conditions so that soil water is conserved for use later in the growing season. While genetic variation for this trait has been identified within several crop species, such varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 19 publications
5
86
1
Order By: Relevance
“…Manipulating ABA metabolism, signaling, and the regulation of the pathway provides an opportunity to not only enhance the plants' response to drought stress by increasing its sensitivity and amplifying its magnitude but also modulate the plant's water economy. By preventing excessive transpiration and maintaining close to normal photosynthesis under well-watered conditions, plants can decrease water removal from the soil so that soil water is conserved and available during periods of stress (Gholipoor et al, 2013;Messina et al, 2015). We show that such a trait (Fig.…”
Section: Maize Drought Tolerance Improvement Via Overexpression Of Zmmentioning
confidence: 71%
“…Manipulating ABA metabolism, signaling, and the regulation of the pathway provides an opportunity to not only enhance the plants' response to drought stress by increasing its sensitivity and amplifying its magnitude but also modulate the plant's water economy. By preventing excessive transpiration and maintaining close to normal photosynthesis under well-watered conditions, plants can decrease water removal from the soil so that soil water is conserved and available during periods of stress (Gholipoor et al, 2013;Messina et al, 2015). We show that such a trait (Fig.…”
Section: Maize Drought Tolerance Improvement Via Overexpression Of Zmmentioning
confidence: 71%
“…All information used to define the prior parameters was based on published information for maize. For the VPDB trait, the results reported by Gholipoor et al (2013) were used. For TUS, the prior parameters were determined based on a combination of published information indicating a TUS interval of 3 d ) and field observations indicating synchronous termination of leaf expansion and commencement of shedding for drought tolerant hybrids.…”
Section: Approximate Bayesian Computationmentioning
confidence: 99%
“…Considerable evidence has confirmed that the limitedtranspiration trait, assessed under well-watered conditions, is expressed in selected genotypes of several crop species, including soybean [12,20,40,45,60], peanut (Arachis hypogaea L.) [3,47], sorghum [19,24,39,48], chickpea (Cicer arietinum L.) [68], pearl millet [22], cowpea (Vigna unguiculata L.) [1], maize (Zea mays L.) [18,67], and wheat [38,44]. With regard to lentil, no information is available to date on diversity among lentil genotypes in the transpiration response to vapor pressure deficit (VPD).…”
Section: Partial Stomatal Closure Under High Atmospheric Vapor Pressumentioning
confidence: 99%